(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The fundamental role of communication in the sphere of state and municipal administration is indisputable, since its effectiveness directly affects the fulfillment by state bodies of their immediate tasks and the achievement of state goals set for them. However, the very problem of the importance of effective communication has not been sufficiently worked out in the civil service, taking into account the specifics of all its elements. The article deals with issues related to the specifics of achieving effective communication in the work of public authorities and local self-government on the adoption and execution of managerial decisions, interaction of civil servants, their preservation of a positive image of authorities in the process of communication.